Nature’s pre-installed helpers: diverse seed endophytes enhance rice nitrogen use efficiency - Lao, Ruimin; Fang, Shaoxing; Fang, Wenjun; Zhao, Zhiwei; Li, Haiyan; Li, Tao (Frontiers in Plant Science, 2026)
Nitrogen is a key limiting factor for crop growth, and improving nitrogen use efficiency (NUE) is critical for achieving high crop yields. In this study, both culture-independent and culture-dependent approaches were employed to systematically analyze the community composition and functional traits of seed endophytic bacteria in rice varieties with contrasting NUE. The results revealed diverse endophytic bacterial communities across the four rice varieties, with Shannon indices ranging from 2.95 to 3.23. However, significant compositional differences were observed among varieties. Rare taxa accounted for over 51% of operational taxonomic units (OTUs) in each variety and were the primary drivers of community diversity and differentiation. In contrast, core taxa (shared OTUs) were highly conserved across varieties, largely composed of abundant taxa (OTUs > 39%, total relative abundance > 93%), and occupied central positions in co-occurrence networks, thereby contributing to community stability. Five representative strains exhibited diverse plant growth-promoting (PGP) traits in vitro, including siderophore production, phosphate solubilization, and indole - 3 - acetic acid (IAA) synthesis. These functions were partially redundant, but individual strains exhibited distinct strengths, indicating functional complementarity. Inoculation experiments demonstrated that all strains improved rice growth, nitrogen accumulation, and NUE, with their effectiveness modulated by both strain identity and nitrogen availability. This study reveals rice seed endophytic bacteria as “natural microbial allies” that support host growth and adaptation under low-nitrogen conditions. These endophytes represent valuable microbial resources for the development of next-generation biofertilizers in sustainable agriculture.